Interaction of Spin-Labeled Inhibitors of the Vacuolar H(+)-ATPase with the Transmembrane V(o)-Sector - Dixon, Neil (The Biophysical Society, 2008)
The osteoclast variant of the vacuolar H(+)-ATPase (V-ATPase) is a potential therapeutic target for combating the excessive bone resorption that is involved in osteoporosis. The most potent in a series of synthetic inhibitors based on 5-(5,6-dichloro-2-indolyl)-2-methoxy-2,4-pentadienamide (INDOL0) has demonstrated specificity for the osteoclast enzyme, over other V-ATPases. Interaction of two nitroxide spin-labeled derivatives (INDOL6 and INDOL5) with the V-ATPase is studied here by using the transport-active 16-kDa proteolipid analog of subunit c from the hepatopancreas of Nephrops norvegicus, in conjunction with electron paramagnetic resonance (EPR) spectroscopy. Analogous experiments are also performed with vacuolar membranes from Saccharomyces cerevisiae, in which subunit c of the V-ATPase is replaced functionally by the Nephrops 16-kDa proteolipid. The INDOL5 derivative is designed to optimize detection of interaction with the V-ATPase by EPR. In membranous preparations of the Nephrops 16-kDa proteolipid, the EPR spectra of INDOL5 contain a motionally restricted component that arises from direct association of the indolyl inhibitor with the transmembrane domain of the proteolipid subunit c. A similar, but considerably smaller, motionally restricted population is detected in the EPR spectra of the INDOL6 derivative in vacuolar membranes, in addition to the larger population from INDOL6 in the fluid bilayer regions of the membrane. The potent classical V-ATPase inhibitor concanamycin A at high concentrations induces motional restriction of INDOL5, which masks the spectral effects of displacement at lower concentrations of concanamycin A. The INDOL6 derivative, which is closest to the parent INDOL0 inhibitor, displays limited subtype specificity for the osteoclast V-ATPase, with an IC(50) in the 10-nanomolar range.